Building Pacifist Character: Islamic Peace Education for Indonesian Youth in Divided Communities - Khisbiyah, Yayah; Thoyibi, M.; Aly, Abdullah; Santoso, M. Fattah; Baidhawy, Zakiyuddin (Faculty of Psychology, Universitas Surabaya, 2012)
The ideological and political agenda of different groups are often put forward by way of hate speech and intolerant messages towards members of different ethno-religious groups. In this context, religious education could play a key part in promoting more positive views about diversity. This article presents an investigation into the curriculum of existing Islamic Religious Education in four junior high schools in Solo, as well as teachers and students’ perceptions regarding religious diversity. The research results show that the curriculum lacks content that aims at co-existence and peace education. Also, around a third of the teachers and students reported intolerant attitudes towards different religions. The results were then followed up by a pilot project to develop the Islam-based Peace Education (IPE), which aims at building pacifist character in youth, through teaching mutual respect, non-violence, social justice, and co-existence, by using Islamic values derived from al-Qur’an andSunnah. Kepentingan ideologis dan politik berbagai golongan dalam memperebutkan kuasa ditengarai telah membuat masyarakat terpecah-belah oleh perbedaan etnis dan agama, sehingga rentan terhadap ketegangan antarkelompok, konflik, dan bahkan kekerasan berdarah, termasuk yang sering terjadi pada masyarakat majemuk di kota Solo. Dalam konteks ini, pendidikan agama memegang peran kunci untuk membentuk sikap yang lebih toleran terhadap perbedaan. Artikel ini meneliti muatan kurikulum Pendidikan Agama Islam di empat SMP di Solo, dan persepsi guru serta peserta didik tentang keanekaragaman agama dan budaya. Hasil penelitian menemukan bahwa muatan kurikulum yang mengajarkan hidup berdampingan dalam keanekara- gaman secara damai ternyata masih kurang memadai, Sekitar sepertiga guru dan siswa ditengarai memiliki sikap intoleran terhadap perbedaan agama. Hasil penelitian ini ditindaklanjuti dengan program rintisan Pendidikan Perdamaian Berbasis Islam (PPBI) yang bertujuan mensosialisasikan nilai-nilai keadilan, nir- kekerasan, dan perdamaian sebagaimana diajarkan Islam melalui dua sumber utamanya, al-Qur’an danSunnah.